The Fourrée Hyperpyra of John V Palaeologus - Cowell, Sam (KOINON: The International Journal of Classical Numismatic Studies, 2023)
The great revival and reconquests undertaken by Andronikos III Palaeologus were shattered upon his death. Erstwhile allies and family turned on each other in the wake of the premature death of the emperor, with deadly intrigue undertaken for who should control the regency of young John V, heir of the late Basileus. Campaigns in the previous decade that were successfully restoring northern Greece and the Balkans into Byzantine hands were at once abandoned when private dispute spilled over into civil war. On the one side stood the foreign mother of the young emperor, Anna of Savoy. On the other stood John Cantacuzene, best friend and right-hand man of John V’s father. At stake was a squabbling patchwork of semi-independent statelets with various degrees of allegiance to the empire. During a period when the empire could ill afford it, precious resources were squandered on in-fighting. When John Cantacuzene found himself the brief winner of the civil war before his subsequent deposition, he no longer dined on dishes of silver and gold but pewter. The crown jewels of the empire had been pawned away to Venice and the riches of the Romans wasted away on fighting that only hurt the Romans themselves. Thus, riding out from his palace in the finest bejeweled splendor the heirlooms of late antiquity had to offer, the emperor returned home wearing a glass crown. From an empire on the rebound in 1341, Byzantium was shattered and near fatally weakened in 1353.